The Concept of Ulul Albab in the Qur'an (Analysis of QS. Az-Zumar Verse 9) - Isri Lailatussa’idah; Ibnu Rusydi (Aslama: Journal of Islamic Studies, 2024)
There are many verses in the Qur'an that explain thinking, because humans are given reason and thoughts so that humans can think. In relation to people who have reason, the Qur'an mentions ulul albab, meaning people who have reason, meaning that humans use reason in a pure way that is not clouded by lust. There are quite a few people who are knowledgeable but do not use their minds, they are dominated by lust and do not accept the truth of the Qur'an or As-Sunnah so that their hearts are hardened to stone, their minds are dirty and they do not use their common sense. In connection with this, the author is interested in providing an article regarding the concept of ulul albab based on the background of this problem. The aim of this research is to understand the concept of Ulul Albab in the Al-Qur'an (Analysis of Qs. Az-Zumar Verse 9). The research method is qualitative with library research analysis. The results of this research are that the position of ulul albab is that they have a willingness to convey their knowledge to others. The ulul albab have a responsibility to improve society and are called upon to be pioneers in creating benefits in society.